Editor Cooperativo para Diagramação de Software OO - Dias, Márcio de Sousa; Xexéo, Geraldo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1997: Anais do XI Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1997.24072, 1997)
Complex software development requires an effective interaction among several specialists. This interaction can only be effective with the support of collaborative tools. This article presents a collaborative editor to support the diagramming activities of object oriented software modeling, describing the first version, where we exploited some synchronous aspects of the interaction.